2004
DOI: 10.1097/01.prs.0000138253.96709.e5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Ablated Rat Rectus Abdominis by Muscle Regeneration

Abstract: Skeletal muscle regeneration is a powerful, naturally occurring process of tissue reconstruction that follows myofiber damage secondary to myotoxic injury that does not normally affect the tissue circulation and scaffold. The ablated tissue, in traumatology and free muscle grafts, is frequently replaced by scars. The final outcome is poor even after in situ myoblast seeding of the harvested muscle. The goal of this study was to identify protocols to reconstruct muscle tissue, even in such adverse environments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
(26 reference statements)
3
14
0
Order By: Relevance
“…Moreover, evidence suggests that the procedures used for isolation and in vitro expansion can cause satellite cells to lose their regenerative capacity (Renault et al 2000;Sherwood and Wagers 2006;Montarras et al 2005), with some suggesting the use of muscle grafts to provide a satellite cell population rather than enzymatic isolation techniques (Montarras et al 2005;Collins and Zammit 2009;Mong 1988;Schultz et al 1988). Despite these problems, a number of examples of satellite cell transplantation have led to the successful restoration of muscle injuries (Alameddine et al 1989;Alameddine et al 1994;el Andalousi Boubaker et al 2002;Li et al 2010;Marzaro et al 2002;Vindigni et al 2004). …”
Section: Recruitment Of Myogenic Progenitor Cellsmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, evidence suggests that the procedures used for isolation and in vitro expansion can cause satellite cells to lose their regenerative capacity (Renault et al 2000;Sherwood and Wagers 2006;Montarras et al 2005), with some suggesting the use of muscle grafts to provide a satellite cell population rather than enzymatic isolation techniques (Montarras et al 2005;Collins and Zammit 2009;Mong 1988;Schultz et al 1988). Despite these problems, a number of examples of satellite cell transplantation have led to the successful restoration of muscle injuries (Alameddine et al 1989;Alameddine et al 1994;el Andalousi Boubaker et al 2002;Li et al 2010;Marzaro et al 2002;Vindigni et al 2004). …”
Section: Recruitment Of Myogenic Progenitor Cellsmentioning
confidence: 93%
“…The seeding of an ECM scaffold with myogenic progenitor cells, followed by transfer to an in vivo site, allows the full development of myotubes and functional muscle tissue to occur (Liao and Zhou 2009;Borschel et al 2004;du Moon et al 2008;Vindigni et al 2004;Beier et al 2009;Merritt et al 2010). However, these in vitro techniques generally produce muscle with small contractile forces, since the amount of scaffold material is high and can inhibit myoblast fusion.…”
Section: Control Of the Regenerative Microenvironmentmentioning
confidence: 98%
“…The ontogenesis of these EPCs is unclear, however they may derive from putative hemangioblasts which are the precursors of both hematopoietic and endothelial cell lineages (Vindigni et al, 2004). These hemangioblasts express phenotypic markers of hematopoietic stem cells (HSCs) and differentiated endothelial cells, CD34/Flk-1 (Vindigni et al, 2004) and are difficult to distinguish from EPCs. Once in peripheral blood they home to sites of tumor growth, where they differentiate into endothelial cells to support vascular remodeling (Asahara et al, 1999).…”
Section: Cancer Stem Cells and Their Role In Forming The Tumor Micro-mentioning
confidence: 98%
“…It has been shown that BM-derived endothelial progenitor cells (EPCs) as the leading cellular component in tumor angiogenesis (Lyden et al, 2001). The ontogenesis of these EPCs is unclear, however they may derive from putative hemangioblasts which are the precursors of both hematopoietic and endothelial cell lineages (Vindigni et al, 2004). These hemangioblasts express phenotypic markers of hematopoietic stem cells (HSCs) and differentiated endothelial cells, CD34/Flk-1 (Vindigni et al, 2004) and are difficult to distinguish from EPCs.…”
Section: Cancer Stem Cells and Their Role In Forming The Tumor Micro-mentioning
confidence: 99%
“…Until now, successes have been restricted to relatively thin or avascular structures (for example, skin and cartilage), where postimplantation neovascularization from the host is sufficient to meet the implant's demand for oxygen and nutrients. [4][5][6][7][8] Few manuscripts describe the construction of an adipose tissue composite flap that could be used to reconstruct volume-significant soft tissue lost to cancer, trauma, or deep burn. 9 -13 In particular, as surgical mastectomy or lumpectomy for treatment of breast cancer is frequently performed, there is a significant need for breast reconstruction.…”
mentioning
confidence: 99%